Successful Treatment of a Drug-Resistant Epilepsy by Long-term Transcranial Direct Current Stimulation: A Case Report - San-Juan, Daniel; Sarmiento, Carlos Ignacio; González, Katia Márquez; Orenday Barraza, José Manuel (Frontiers in Neurology, 2018)
Transcranial direct current stimulation (tDCS) is a reemerged noninvasive cerebral therapy used to treat patients with epilepsy, including focal cortical dysplasia, with controversial results. We present a case of a 28-year-old female with left frontal cortical dysplasia refractory to antiepileptic drugs, characterized by 10–15 daily right tonic hemi-body seizures. The patient received a total of seven sessions of cathodal tDCS (2 mA, 30 min). The first three sessions were applied over three consecutive days, and the remaining four sessions of tDCS were given each at 2-week intervals. At the 1-year follow-up, the patient reported to have a single seizure per month and only mild adverse events.